Educação no trabalho: retendo talentos na organização - o caso da Petrobrás - Macedo, Ivanildo Izaias de (1998)
This dissertation has the purpose of verifying what kinds of education promote the talents retention inside studied company. Thus, a conceitual structure has been built based on studies divulgated by specialists in companies, in education, and by humanits philosophists. This theoretic reference shows that factors such as power amount, thf access to information, the payment and the education give for the company, influence in the talents decision for the permanence in the organization. And it has inspired the delimitation and the construction of the researches suppositions and conceptual model bringing together the kinds of educations at work, the kinds of resources development, the works motivation and the talents retention too. The results comparison analyis to the formulated suppositions served to improved the conceitual model, and for us to conclude that the technical, personal and organization educations have the tendency of generating financiai, individual and institucional motivations that, in their own, will produce significant effects on the company's talents retention.